Educational proposals from archaeology: experiences of the ITAIPU Tierra Guaraní MUSEUM - Alfonso Monges, Mirtha (Museo de Antropología de Entre Ríos, 2023)
The construction of the ITAIPU dam, begun in 1975, brought with it a range of changes to the Alto Paraná region. Already in the feasibility studies, carried out at the end of the 1960s and the beginning of the 1970s, the existence of diverse archaeological heritage in the area of ​​influence of the work was mentioned. This motivated the creation of a multidisciplinary research plan with the aim of surveying archaeological contexts and obtaining as much information and material evidence as possible that, otherwise, would be lost with the creation of the reservoir. Within the framework of these studies, the initial guidelines were established for the fitting out of a museum that houses these valuable collections and contextualizes them for scientific and educational purposes. The last couple of years, the implementation of experimental workshops aimed especially at children and adolescents, emerged as a response to the need to spread the importance of archeology as a necessary science for social construction, to make visible the scientific work of professionals, whose role and scope is not often clear to the communities, and to present the pre-Hispanic period in a different light than what is normally taught in the classroom. This article proposes an approach to these experiences of working with the public through the archaeological collection of the museum.